Salt-spray-resistant high-strength aluminum alloy and preparation method thereof

By spraying the aluminum alloy surface to refractive epoxy resin spraying liquid to form a high -intensity aluminum alloy salt -resistant and fog, solve the problem of corrosive sensitivity in aluminum alloy in the ocean atmospheric environment, and achieve the effect of significantly improve the corrosion resistance and mechanical strength Essence

CN119352126AInactive Publication Date: 2025-01-24BEIJING JUJIA MASCH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411466531.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In marine atmospheric environments, the corrosion sensitivity of aluminum alloy structural parts is increased, resulting in a decrease in service life and safety, and it is difficult for the prior art to effectively improve their corrosion resistance.

Method used

Spray the modified epoxy resin spraying on the surface of the microcrack oxide alloy to make a salt -resistant high -strength aluminum alloy. Modified epoxy resin spraying solution is composed of epoxy amine monomers, epoxy resin, modified basalt fiber, water -free ethanol, amino seizure monomer, polyetherine, etc., and solid coating.

Benefits of technology

It significantly improves the anti -salt fog corrosion performance and mechanical strength of aluminum alloy, prolongs the service life, and enhances the surface hydrophobic performance and self -repairing ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005093498260000041
    Figure BDA0005093498260000041
  • Figure BDA0005093498260000042
    Figure BDA0005093498260000042
  • Figure BDA0005093498260000111
    Figure BDA0005093498260000111
Patent Text Reader

Abstract

The invention discloses a salt-spray-resistant high-strength aluminum alloy and a preparation method thereof, and relates to the technical field of alloy materials. When the salt-spray-resistant high-strength aluminum alloy is prepared, firstly, 5-hydroxymethylfurfural reacts with decamethylene diamine and then reacts with epichlorohydrin to prepare an epoxidized imine monomer; the preparation method comprises the following steps: reacting m-aminophenol with ethyl acetoacetate to prepare an aminocoumarin monomer; the preparation method comprises the following steps: pretreating basalt fibers, activating, and modifying with a coupling agent to obtain modified basalt fibers; the method comprises the following steps: pretreating an aluminum alloy, and carrying out micro-arc oxidation to obtain a micro-arc oxidation aluminum alloy; preparing modified epoxy resin spraying liquid from an epoxidized imine monomer, epoxy resin, an aminocoumarin monomer, polyether amine, the modified basalt fiber and ethyl alcohol, and spraying the surface of the micro-arc oxidation aluminum alloy with the modified epoxy resin spraying liquid to prepare the salt-spray-resistant high-strength aluminum alloy. The prepared salt-fog-resistant high-strength aluminum alloy has the advantages of salt fog resistance, self-repairing, hydrophobicity, high impact strength and good surface bonding strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a salt spray resistant high-strength aluminum alloy and a preparation method thereof. Background Art

[0002] The loss of resources and energy consumption caused by material corrosion has become an increasingly difficult problem to ignore, and has become one of the key factors restricting economic growth and sustainable development of human society.

[0003] Atmospheric corrosion refers to the phenomenon that materials are irreversibly damaged and deteriorated in the atmospheric environment. It is one of the most common types of corrosion. Atmospheric conditions such as relative humidity, temperature, sunshine time, pollutants, salinity, etc. play an important role in the corrosion of exposed metals. In particular, for facilities serving in the marine atmosphere, high humidity and high salinity in the air put forward more stringent requirements on the service life and safety of metal components.

[0004] Aluminum alloys are widely used due to their light weight, high specific strength, easy processing and excellent electrical properties. Aluminum alloys usually have excellent corrosion resistance because their surface is covered with a dense oxide film. However, in the marine environment, the atmosphere contains a lot of salt and high relative humidity, which greatly increases the corrosion sensitivity of aluminum alloys, resulting in a significant decrease in the service life and safety of aluminum alloy structural parts. A large number of marine atmospheric corrosion studies on aluminum alloys have been carried out at home and abroad.

[0005] Since the electrode potential of aluminum alloy itself is relatively low, when the alloy is in contact with other metals, it is more likely to act as an anode and electrochemically corrode. Therefore, certain surface treatments must be performed on the surface of aluminum alloy to improve its corrosion resistance, friction resistance, scratch resistance and other properties, such as surface ceramic processes such as anodizing and coating processes such as spray painting. At the same time, in addition to high requirements for decorative properties, the surface film layer also has the highest requirements for wind erosion resistance, impact resistance, salt spray resistance, etc. Summary of the invention

[0006] The object of the present invention is to provide a salt spray resistant high-strength aluminum alloy and a preparation method thereof, so as to solve the problems existing in the prior art.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0008] A salt spray resistant high-strength aluminum alloy, wherein the salt spray resistant high-strength aluminum alloy is prepared by spraying a modified epoxy resin spray liquid on a micro-arc oxidation aluminum alloy surface;

[0009] The micro-arc oxidation aluminum alloy is prepared by pre-treating the aluminum alloy and then subjecting it to micro-arc oxidation process;

[0010] The modified epoxy resin spraying liquid is prepared by mixing epoxide imine monomer, epoxy resin, modified basalt fiber, anhydrous ethanol, aminocoumarin monomer and polyetheramine;

[0011] The epoxide imine monomer is prepared by reacting 5-hydroxymethylfurfural with decanediamine and then with epichlorohydrin;

[0012] The modified basalt fiber is prepared by activating the basalt fiber after pretreatment and then modifying it with a coupling agent;

[0013] The aminocoumarin monomer is prepared by reacting m-aminophenol with ethyl acetoacetate.

[0014] As an optimization, the aluminum alloy is a 7xxx series aluminum alloy.

[0015] As an optimization, the epoxy resin model is E-51, and the polyetheramine model is polyetheramine D-230.

[0016] A method for preparing a salt spray resistant high-strength aluminum alloy comprises the following preparation steps:

[0017] (1) The aluminum alloy is cut into the specified specifications of the product, and polished step by step under the conditions of 60#, 300#, 1000#, and 2000# sandpaper until the surface of the sample is free of scratches and smooth, and then ultrasonically cleaned and degreased with acetone solution, rinsed with ethanol and deionized water, and dried to obtain aluminum alloy samples;

[0018] (2) Immerse the aluminum alloy sample in the electrolyte, connect the circuit, turn on the cooling water, set the parameters according to the micro-arc oxidation process requirements, start micro-arc oxidation, remove the cooling water after the reaction is completed, turn off the power and take it out, ultrasonically clean it in pure water for 3 to 4 times, each time for 8 to 10 minutes, and dry it in an oven at 100 to 120° C. for 8 to 10 hours to obtain a micro-arc oxidized aluminum alloy;

[0019] (3) Melting 26 to 28 parts of 5-hydroxymethylfurfural at 50 to 60° C. by mass, adding 17 to 18 parts of decanediamine in 8 to 10 portions, reacting at 105 to 110° C. and 200 to 300 r / min for 1 to 1.5 hours after all the addition, cooling naturally to room temperature, washing with pure water and petroleum ether for 2 to 3 times respectively, and vacuum drying at 80 to 90° C. for 10 to 12 hours to obtain an imine monomer;

[0020] (4) By weight, 45-46 parts of epichlorohydrin, 48-49 parts of imine monomer, and 0.8-0.9 parts of tetrabutylammonium bromide were mixed uniformly, reacted at 80-85° C. and 300-400 r / min for 2-3 hours, cooled naturally to room temperature, and 24-25 parts of 40wt% sodium hydroxide solution were added dropwise within 30 minutes, and 25-28 parts of butyl acetate were added at the same time. After the addition was completed, stirring was continued for 1-1.5 hours, filtered, and the filtrate was reprecipitated with petroleum ether and then filtered. All precipitates were washed once with ethanol, and then washed 3-4 times with pure water, and vacuum dried at 70-80° C. for 8-10 hours to obtain an epoxy imine monomer;

[0021] (5) By weight, 10.9-11.7 parts of m-aminophenol are dissolved in 40-45 parts of dioxane, 5-6 parts of concentrated sulfuric acid are added dropwise at a rate of 1-2 drops per second, and 13-14 parts of ethyl acetoacetate are added dropwise at the same rate, and the mixture is reacted at 60-70° C. in a water bath at 300-400 r / min for 6-8 hours, cooled naturally to room temperature, and then precipitated in an ice water bath for 2-3 hours, filtered, and vacuum dried at 60-70° C. for 6-8 hours, recrystallized with ethyl acetate, and then vacuum dried once to obtain an aminocoumarin monomer;

[0022] (6) By weight, 10 to 15 parts of the pretreated basalt fiber and 90 to 100 parts of the activation solution were mixed evenly, stirred at 80 to 90° C. and 300 to 400 r / min for 2 to 3 hours, filtered, ultrasonically cleaned with pure water for 3 to 4 times, each time for 4 to 5 minutes, and dried in an oven at 105 to 110° C. for 10 to 12 hours to obtain activated basalt fiber;

[0023] (7) Add 10 to 15 parts of activated basalt fiber to 80 to 90 parts of coupling agent solution by weight, ultrasonically disperse for 20 to 30 minutes, stir at 70 to 75° C. and 200 to 300 r / min for 4 to 5 hours, filter, wash with pure water for 3 to 5 times, and vacuum dry at 80 to 90° C. for 8 to 10 hours to obtain modified basalt fiber;

[0024] (8) By weight, 2 to 3 parts of epoxide imine monomer, 3 to 4 parts of epoxy resin, 1.5 to 2 parts of modified basalt fiber, and 70 to 80 parts of anhydrous ethanol are mixed uniformly, and ultrasonically dispersed at room temperature for 50 to 60 minutes, and 1 to 2 parts of aminocoumarin monomer and 2 to 3 parts of polyetheramine are added, and ultrasonically dispersed at room temperature for 30 to 40 minutes to prepare a modified epoxy resin spray liquid;

[0025] (9) The modified epoxy resin spray liquid is sprayed on the surface of the micro-arc oxidized aluminum alloy with a spray gun, the spraying distance is controlled at 10 to 15 cm, the spraying pressure is 0.3 MPa, the coating thickness is controlled at 140 to 160 μm, and after spraying, it is cured at a constant temperature of 60° C. for 40 to 48 hours to obtain a salt spray resistant high-strength aluminum alloy.

[0026] As an optimization, the electrolyte in step (2) includes the following components: 9-10 g / L sodium silicate, 3-4 g / L sodium hydroxide, 1-1.5 g / L sodium fluoride, 0.02 mol / L 3-aminopropyltriethoxysilane, and 2 g / L hydrogen peroxide.

[0027] As an optimization, the micro-arc oxidation process parameters in step (2) are mainly: using a pulse power supply, a unidirectional pulse mode, and a current density of 8 to 10 A / dm 3 , time 30~40min, frequency 500Hz, duty cycle 10%.

[0028] As an optimization, the imine monomer reaction process in step (3) is as follows:

[0029]

[0030] As an optimization, the reaction process of the epoxide imine monomer in step (4) is as follows:

[0031]

[0032] As an optimization, the aminocoumarin monomer reaction process in step (5) is as follows:

[0033]

[0034] As an optimization, the pretreatment process of the basalt fiber in step (6) is to crush it with a crusher and screen out basalt fibers with a length of 100 to 200 μm with a screen.

[0035] As an optimization, the activation solution in step (6) is prepared by mixing 98 wt % concentrated sulfuric acid and 30 wt % hydrogen peroxide solution in a volume ratio of 7:3.

[0036] As an optimization, the coupling agent solution in step (7) is prepared by uniformly mixing anhydrous ethanol, pure water, 3-aminopropyltriethoxysilane and dodecyltriethoxysilane in a mass ratio of 90:10:1:1 and then ultrasonically dispersing for 3 to 5 minutes.

[0037] As an optimization, the modified epoxy resin spray liquid in step (8) can also be prepared into corresponding coatings according to the process requirements of scraping, dripping and brushing, and applied by scraping, dripping and brushing.

[0038] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0039] When preparing the salt-spray resistant high-strength aluminum alloy, the present invention comprises the following steps: firstly reacting 5-hydroxymethylfurfural with decanediamine and then reacting with epichlorohydrin to obtain an epoxidized imine monomer; reacting m-aminophenol with ethyl acetoacetate to obtain an aminocoumarin monomer; pre-treating basalt fiber and then activating it and then modifying it with a coupling agent to obtain a modified basalt fiber; pre-treating the aluminum alloy and performing micro-arc oxidation to obtain a micro-arc oxidized aluminum alloy; preparing a modified epoxy resin spraying liquid by mixing the epoxidized imine monomer, epoxy resin, aminocoumarin monomer, polyetheramine, modified basalt fiber and ethanol, and spraying the modified epoxy resin spraying liquid on the surface of the micro-arc oxidized aluminum alloy to obtain the salt-spray resistant high-strength aluminum alloy.

[0040] First, 5-hydroxymethylfurfural reacts with decanediamine to form an imine bond by Schiff base reaction, and then epichlorohydrin is used to react with the hydroxyl groups on it for epoxidation, and epoxy groups are introduced thereto for subsequent cross-linking and curing of the epoxy resin. At the same time, the imine bond is a dynamic covalent bond, and exchange reactions between imine-amino and imine-imine can occur at room temperature, thereby achieving a macroscopic self-repairing function, and the imine bond can also effectively improve the corrosion resistance due to its intrinsic anti-corrosion properties; m-aminophenol reacts with ethyl acetoacetate to form an amino-substituted coumarin monomer, and the amino group at the substituted position can react with the epoxy group to be introduced into the epoxy resin system, while the coumarin group has the characteristic of reversible photodimerization, and can undergo reversible photodimerization and photodissociation reactions under different ultraviolet light conditions. The reversible photodimerization property gives it reversible self-healing properties; basalt fiber is inexpensive and can effectively improve the corrosion resistance and mechanical properties of epoxy resin coatings as a filler. However, as an inorganic fiber, basalt fiber is difficult to disperse evenly, which will lead to uneven strength. Therefore, it is first activated and then modified with long carbon chain siloxane and aminosiloxane. The activated basalt fiber has more reaction sites, making the subsequent modification more sufficient. The introduction of amino groups allows it to react with the epoxy groups in the epoxy resin to form covalent bonds, which improves the mechanical properties while also improving the corrosion resistance and hydrophobic properties. The introduction of long carbon chains on the surface improves its dispersibility in epoxy resin on the one hand, and the hydrophobic properties of the epoxy resin coating on the other hand.

[0041] Secondly, the micro-arc oxidation process can form a wear-resistant and corrosion-resistant ceramic film layer on the surface of the aluminum alloy. In the micro-arc oxidation process, 3-aminopropyltriethoxysilane is introduced into the electrolyte. The arc discharge phenomenon can be effectively suppressed during the micro-arc oxidation process, and the number and width of microcracks in the micro-arc oxidation film layer can be reduced, thereby improving the performance of the micro-arc oxidation film layer. At the same time, due to the limitations of the micro-arc oxidation process, the microcrack defects cannot be completely eliminated. The addition of 3-aminopropyltriethoxysilane in the electrolyte can also introduce amino groups into the micro-arc oxidation film layer.

[0042] Finally, the prepared epoxide imine monomer and aminocoumarin monomer are mixed with commercially available epoxy resin and polyetheramine curing agent, filler-modified basalt fiber is added, and anhydrous ethanol is used to prepare a spray liquid, which is then applied to the surface of the micro-arc oxidized aluminum alloy by spraying. The amino groups introduced in the surface film layer of the micro-arc oxidized aluminum alloy can react with epoxy groups to form a covalent bond connection, which improves the bonding strength of the coating. The microcracks on the surface of the micro-arc oxidation film layer are intricate, and the epoxy resin coating sprayed on it can effectively seal the pores and penetrate deep into the microcracks. After curing, a physical locking structure is formed, which effectively improves the adhesion of the coating and reduces the probability of the coating falling off during use. DETAILED DESCRIPTION

[0043] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] The raw materials and process information used in all the following examples and comparative examples are as follows:

[0045] Aluminum alloy: 7075 aluminum alloy, purchased from Northeast Light Alloy Co., Ltd.;

[0046] Epoxy resin: E-51 epoxy resin, purchased from Nantong Xingchen Synthetic Materials Co., Ltd.;

[0047] Polyetheramine: Polyetheramine D-230, purchased from Wuxi Akeli Technology Co., Ltd.;

[0048] Basalt fiber: diameter 13 μm, length 3 mm, purchased from Sichuan Tianrun Basalt Technology Co., Ltd.;

[0049] The electrolyte used had a formula of: 9 g / L sodium silicate, 3 g / L sodium hydroxide, 1 g / L sodium fluoride, 0.02 mol / L 3-aminopropyltriethoxysilane, and 2 g / L hydrogen peroxide;

[0050] The micro-arc oxidation process parameters are: pulse power supply, unidirectional pulse mode, current density 10A / dm 3 , time 30min, frequency 500Hz, duty cycle 10%;

[0051] Basalt pretreatment process: crush with a crusher, and use a screen to screen out basalt fibers with a length of 140 to 160 μm;

[0052] Activation solution: 98wt% concentrated sulfuric acid and 30wt% hydrogen peroxide solution were mixed in a volume ratio of 7:3;

[0053] Coupling agent solution: anhydrous ethanol, pure water, 3-aminopropyltriethoxysilane and dodecyltriethoxysilane were mixed uniformly in a mass ratio of 90:10:1:1 and then ultrasonically dispersed for 5 minutes to prepare the coupling agent solution.

[0054] Embodiment 1:

[0055] A method for preparing a salt spray resistant high-strength aluminum alloy, the method for preparing a salt spray resistant high-strength aluminum alloy comprising the following preparation steps:

[0056] (1) The aluminum alloy is cut into the specified specifications of the product, and polished step by step under the conditions of 60#, 300#, 1000#, and 2000# sandpaper until the surface of the sample is free of scratches and smooth, and then ultrasonically cleaned and degreased with acetone solution, rinsed with ethanol and deionized water, and dried to obtain aluminum alloy samples;

[0057] (2) Immerse the aluminum alloy sample in the electrolyte, connect the circuit, turn on the cooling water, set the parameters according to the micro-arc oxidation process requirements, start micro-arc oxidation, remove the cooling water after the reaction is completed, turn off the power and take it out, ultrasonically clean it in pure water for 3 times, each time for 10 minutes, and dry it in a 100°C oven for 10 hours to obtain a micro-arc oxidized aluminum alloy;

[0058] (3) By weight, 26 parts of 5-hydroxymethylfurfural were melted at 50° C., and 17 parts of decanediamine were added in 8 portions. After all the addition was completed, the mixture was reacted at 105° C. and 200 r / min for 1.5 h, cooled naturally to room temperature, washed twice with pure water and petroleum ether respectively, and dried under vacuum at 80° C. for 10 h to obtain an imine monomer;

[0059] (4) By weight, 45 parts of epichlorohydrin, 48 parts of imine monomer, and 0.8 parts of tetrabutylammonium bromide were mixed uniformly, reacted at 80°C and 300 r / min for 3 hours, cooled naturally to room temperature, and 24 parts of 40wt% sodium hydroxide solution were added dropwise within 30 minutes, and 25 parts of butyl acetate were added at the same time. After the addition was completed, stirring was continued for 1 hour, filtered, and the filtrate was reprecipitated with petroleum ether and then filtered. All precipitates were washed once with ethanol and then washed three times with pure water, and vacuum dried at 70°C for 10 hours to obtain an epoxy imine monomer;

[0060] (5) By weight, 10.9 parts of m-aminophenol were dissolved in 40 parts of dioxane, 5 parts of concentrated sulfuric acid were added dropwise at a rate of 1 drop per second, and 13 parts of ethyl acetoacetate were added dropwise at the same rate, and the mixture was reacted at 300 r / min in a 60° C. water bath for 8 h, cooled naturally to room temperature, and then precipitated in an ice water bath for 2 h, filtered, and vacuum dried at 60° C. for 8 h. After recrystallization with ethyl acetate, the mixture was vacuum dried again to obtain an aminocoumarin monomer;

[0061] (6) 10 parts of pretreated basalt fiber and 90 parts of activation solution were mixed uniformly by weight, stirred at 80°C and 300 r / min for 3 h, filtered, ultrasonically cleaned with pure water 3 times, each time for 4 min, and dried in an oven at 105°C for 12 h to obtain activated basalt fiber;

[0062] (7) By weight, 10 parts of activated basalt fiber were added to 80 parts of coupling agent solution, ultrasonically dispersed for 20 min, stirred at 70 ° C and 200 r / min for 5 h, filtered, washed with pure water for 3 times, and vacuum dried at 80 ° C for 10 h to obtain modified basalt fiber;

[0063] (8) By weight, 2 parts of epoxide imine monomer, 4 parts of epoxy resin, 1.5 parts of modified basalt fiber, and 70 parts of anhydrous ethanol were mixed evenly, and ultrasonically dispersed at room temperature for 50 minutes, and 1 part of aminocoumarin monomer and 3 parts of polyetheramine were added, and ultrasonically dispersed at room temperature for 30 minutes to prepare a modified epoxy resin spray liquid;

[0064] (9) The modified epoxy resin spray liquid is sprayed on the surface of the micro-arc oxidized aluminum alloy with a spray gun, the spraying distance is controlled at 10 cm, the spraying pressure is 0.3 MPa, the coating thickness is controlled at 140 μm, and after spraying, it is cured at a constant temperature of 60° C. for 40 h to obtain a salt spray resistant high-strength aluminum alloy.

[0065] Embodiment 2:

[0066] A method for preparing a salt spray resistant high-strength aluminum alloy, the method for preparing a salt spray resistant high-strength aluminum alloy comprising the following preparation steps:

[0067] (1) The aluminum alloy is cut into the specified specifications of the product, and polished step by step under the conditions of 60#, 300#, 1000#, and 2000# sandpaper until the surface of the sample is free of scratches and smooth, and then ultrasonically cleaned and degreased with acetone solution, rinsed with ethanol and deionized water, and dried to obtain aluminum alloy samples;

[0068] (2) Immerse the aluminum alloy sample in the electrolyte, connect the circuit, turn on the cooling water, set the parameters according to the micro-arc oxidation process requirements, start micro-arc oxidation, remove the cooling water after the reaction is completed, turn off the power and take it out, ultrasonically clean it in pure water for 3 times, each time for 9 minutes, and dry it in an oven at 110°C for 9 hours to obtain micro-arc oxidized aluminum alloy;

[0069] (3) By weight, 27 parts of 5-hydroxymethylfurfural were melted at 55° C., and 17.5 parts of decanediamine were added in 9 portions. After all the addition was completed, the mixture was reacted at 110° C. and 250 r / min for 1 hour, and then naturally cooled to room temperature. The mixture was washed with pure water and petroleum ether twice respectively, and vacuum dried at 85° C. for 11 hours to obtain an imine monomer;

[0070] (4) By weight, 45.5 parts of epichlorohydrin, 48.5 parts of imine monomer, and 0.85 parts of tetrabutylammonium bromide were mixed uniformly, reacted at 80°C and 350 r / min for 2.5 hours, cooled naturally to room temperature, and 24.5 parts of 40wt% sodium hydroxide solution were added dropwise within 30 minutes, and 26 parts of butyl acetate were added at the same time. After the addition was completed, stirring was continued for 1.5 hours, filtered, and the filtrate was reprecipitated with petroleum ether and then filtered. All precipitates were washed once with ethanol and then washed three times with pure water, and vacuum dried at 75°C for 9 hours to obtain an epoxy imine monomer;

[0071] (5) By weight, 11.3 parts of m-aminophenol were dissolved in 42 parts of dioxane, 5.5 parts of concentrated sulfuric acid were added dropwise at a rate of 1.5 drops per second, and 13.5 parts of ethyl acetoacetate were added dropwise at the same rate, and the mixture was reacted at 350 r / min in a 65° C. water bath for 7 h, cooled naturally to room temperature, and then precipitated in an ice water bath for 2.5 h, filtered, and vacuum dried at 65° C. for 7 h. After recrystallization with ethyl acetate, the mixture was vacuum dried again to obtain an aminocoumarin monomer;

[0072] (6) By weight, 12 parts of pretreated basalt fiber and 95 parts of activation solution were mixed evenly, stirred at 85°C and 350 r / min for 2.5 h, filtered, ultrasonically cleaned with pure water 3 times, each time for 5 min, and dried in an oven at 110°C for 11 h to obtain activated basalt fiber;

[0073] (7) By weight, 12.5 parts of activated basalt fiber were added to 85 parts of coupling agent solution, ultrasonically dispersed for 25 min, stirred at 75 ° C and 250 r / min for 4.5 h, filtered, washed with pure water 4 times, and vacuum dried at 85 ° C for 9 h to obtain modified basalt fiber;

[0074] (8) By weight, 2.5 parts of epoxide imine monomer, 3.5 parts of epoxy resin, 1.8 parts of modified basalt fiber, and 75 parts of anhydrous ethanol were mixed evenly, and ultrasonically dispersed at room temperature for 55 minutes, and 1.5 parts of aminocoumarin monomer and 2.5 parts of polyetheramine were added, and ultrasonically dispersed at room temperature for 35 minutes to prepare a modified epoxy resin spray liquid;

[0075] (9) The modified epoxy resin spray liquid is sprayed on the surface of the micro-arc oxidized aluminum alloy with a spray gun, the spraying distance is controlled at 12 cm, the spraying pressure is 0.3 MPa, the coating thickness is controlled at 150 μm, and after spraying, it is cured at a constant temperature of 60° C. for 44 hours to obtain a salt spray resistant high-strength aluminum alloy.

[0076] Embodiment 3:

[0077] A method for preparing a salt spray resistant high-strength aluminum alloy, the method for preparing a salt spray resistant high-strength aluminum alloy comprising the following preparation steps:

[0078] (1) The aluminum alloy is cut into the specified specifications of the product, and polished step by step under the conditions of 60#, 300#, 1000#, and 2000# sandpaper until the surface of the sample is free of scratches and smooth, and then ultrasonically cleaned and degreased with acetone solution, rinsed with ethanol and deionized water, and dried to obtain aluminum alloy samples;

[0079] (2) Immerse the aluminum alloy sample in the electrolyte, connect the circuit, turn on the cooling water, set the parameters according to the micro-arc oxidation process requirements, start micro-arc oxidation, remove the cooling water after the reaction is completed, turn off the power and take it out, ultrasonically clean it in pure water for 4 times, each time for 8 minutes, and dry it in a 120°C oven for 8 hours to obtain a micro-arc oxidized aluminum alloy;

[0080] (3) By weight, 28 parts of 5-hydroxymethylfurfural were melted at 60° C., 18 parts of decanediamine were added in 10 portions, and after all the addition was completed, the mixture was reacted at 110° C. and 300 r / min for 1 hour, cooled naturally to room temperature, washed with pure water and petroleum ether for 3 times respectively, and vacuum dried at 90° C. for 10 hours to obtain an imine monomer;

[0081] (4) By weight, 46 parts of epichlorohydrin, 49 parts of imine monomer, and 0.9 parts of tetrabutylammonium bromide were mixed uniformly, reacted at 85° C. and 400 r / min for 2 h, naturally cooled to room temperature, and 25 parts of 40 wt % sodium hydroxide solution were added dropwise within 30 min, and 28 parts of butyl acetate were added at the same time. After the addition was completed, stirring was continued for 1.5 h, filtered, and the filtrate was reprecipitated with petroleum ether and then filtered. All precipitates were washed once with ethanol and then washed 4 times with pure water, and vacuum dried at 80° C. for 8 h to obtain an epoxy imine monomer;

[0082] (5) By weight, 11.7 parts of m-aminophenol were dissolved in 45 parts of dioxane, 6 parts of concentrated sulfuric acid were added dropwise at a rate of 2 drops per second, and 14 parts of ethyl acetoacetate were added dropwise at the same rate, and the mixture was reacted in a 70°C water bath at 400 r / min for 6 hours, cooled naturally to room temperature, and then precipitated in an ice water bath for 3 hours, filtered, and vacuum dried at 70°C for 6 hours. After recrystallization with ethyl acetate, the mixture was vacuum dried again to obtain an aminocoumarin monomer;

[0083] (6) 15 parts of pretreated basalt fiber and 100 parts of activation solution were mixed uniformly by weight, stirred at 90°C and 400 r / min for 2 h, filtered, ultrasonically cleaned with pure water 4 times, each time for 4 min, and dried in an oven at 110°C for 10 h to obtain activated basalt fiber;

[0084] (7) By weight, 15 parts of activated basalt fiber were added to 90 parts of coupling agent solution, ultrasonically dispersed for 30 min, stirred at 75 ° C and 300 r / min for 4 h, filtered, washed with pure water 5 times, and vacuum dried at 90 ° C for 80 h to obtain modified basalt fiber;

[0085] (8) By weight, 3 parts of epoxide imine monomer, 3 parts of epoxy resin, 2 parts of modified basalt fiber, and 80 parts of anhydrous ethanol were mixed evenly, and ultrasonically dispersed at room temperature for 60 minutes, and 2 parts of aminocoumarin monomer and 2 parts of polyetheramine were added, and ultrasonically dispersed at room temperature for 40 minutes to prepare a modified epoxy resin spray liquid;

[0086] (9) The modified epoxy resin spray liquid is sprayed on the surface of the micro-arc oxidized aluminum alloy with a spray gun, the spraying distance is controlled at 15 cm, the spraying pressure is 0.3 MPa, the coating thickness is controlled at 160 μm, and after spraying, it is cured at a constant temperature of 60° C. for 48 hours to obtain a salt spray resistant high-strength aluminum alloy.

[0087] Comparative Example 1:

[0088] The preparation method of the salt spray resistant high-strength aluminum alloy of Comparative Example 1 is different from that of Example 2 in that steps (3) and (4) are not performed, and step (8) is modified as follows: 6 parts of epoxy resin, 1.8 parts of modified basalt fiber, and 75 parts of anhydrous ethanol are mixed uniformly by mass, ultrasonically dispersed at room temperature for 55 minutes, 1.5 parts of aminocoumarin monomer and 2.5 parts of polyetheramine are added, and ultrasonically dispersed at room temperature for 35 minutes to prepare a modified epoxy resin spray liquid. The remaining steps are the same as those of Example 2.

[0089] Comparative Example 2:

[0090] The preparation method of the salt spray resistant high-strength aluminum alloy of Comparative Example 2 is different from that of Example 2 in that step (5) is not performed, and step (8) is modified as follows: 2.5 parts of epoxide imine monomer, 3.5 parts of epoxy resin, 1.8 parts of modified basalt fiber, and 75 parts of anhydrous ethanol are mixed uniformly by mass, ultrasonically dispersed at room temperature for 55 minutes, 4 parts of polyether amine are added, and ultrasonically dispersed at room temperature for 35 minutes to prepare a modified epoxy resin spray liquid. The remaining steps are the same as those of Example 2.

[0091] Comparative Example 3:

[0092] The preparation method of the salt spray resistant high-strength aluminum alloy of Comparative Example 3 is different from that of Example 2 in that steps (6) and (7) are not performed, and step (8) is modified as follows: 2.5 parts of epoxide imine monomer, 3.5 parts of epoxy resin, and 75 parts of anhydrous ethanol are mixed uniformly by mass, ultrasonically dispersed at room temperature for 55 minutes, 1.5 parts of aminocoumarin monomer and 2.5 parts of polyetheramine are added, and ultrasonically dispersed at room temperature for 35 minutes to prepare a modified epoxy resin spray liquid. The remaining steps are the same as those of Example 2.

[0093] Comparative Example 4:

[0094] The preparation method of the salt spray resistant high-strength aluminum alloy of Comparative Example 4 is different from that of Example 2 in that step (6) is not performed, and step (7) is modified as follows: by weight, 12.5 parts of the pretreated basalt fiber are added to 85 parts of the coupling agent solution, ultrasonically dispersed for 25 minutes, stirred at 75° C. and 250 r / min for 4.5 hours, filtered, washed with pure water 4 times, and vacuum dried at 85° C. for 9 hours to obtain modified basalt fiber. The remaining steps are the same as those of Example 2.

[0095] Comparative Example 5:

[0096] The preparation method of the salt spray resistant high-strength aluminum alloy of Comparative Example 5 is different from that of Example 2 in that steps (6) and (7) are not performed, and step (8) is modified as follows: 2.5 parts of epoxide imine monomer, 3.5 parts of epoxy resin, 1.8 parts of pretreated basalt fiber, and 75 parts of anhydrous ethanol are mixed uniformly by mass, ultrasonically dispersed at room temperature for 55 minutes, 1.5 parts of aminocoumarin monomer and 2.5 parts of polyetheramine are added, and ultrasonically dispersed at room temperature for 35 minutes to prepare a modified epoxy resin spray liquid. The remaining steps are the same as those of Example 2.

[0097] Comparative Example 6:

[0098] The preparation method of the salt spray resistant high-strength aluminum alloy of Comparative Example 6 is different from that of Example 2 in that step (2) is not performed, and step (9) is modified as follows: spraying the modified epoxy resin spray liquid on the surface of the aluminum alloy sample with a spray gun, controlling the spraying distance to 12 cm, the spraying pressure to 0.3 MPa, and the coating thickness to 150 μm, and curing at a constant temperature of 60° C. for 44 hours after spraying to obtain a salt spray resistant high-strength aluminum alloy. The remaining steps are the same as those of Example 2.

[0099] Comparative Example 7:

[0100] The preparation method of the salt spray resistant high-strength aluminum alloy of Comparative Example 7 is different from that of Example 2 in that the electrolyte formula is modified to: 9 g / L sodium silicate, 3 g / L sodium hydroxide, 1 g / L sodium fluoride, and 2 g / L hydrogen peroxide. The remaining steps are the same as those of Example 2.

[0101] Test Example 1:

[0102] Mechanical properties test: The impact strength and adhesion strength of the prepared salt spray resistant high-strength aluminum alloy coating surface are tested to evaluate its mechanical strength. The specific test method is as follows:

[0103] Impact strength: refer to GB / T 1732-2020 to test the impact strength of the coating. Test 5 samples in each group of samples and record the lowest value.

[0104] Bond strength: The bonding strength of the coating is tested in accordance with GB / T 9286-2021. The test results are expressed in grades. Each group of samples is tested 5 times and the lowest grade is recorded.

[0105] The results are shown in Table 1.

[0106] Table 1

[0107]

[0108]

[0109] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 7 in Table 1, it can be found that the salt spray resistant high-strength aluminum alloy prepared in the present invention has higher impact strength and bonding strength.

[0110] A comparison of the data in the table shows that the introduction of epoxide imine monomer, aminocoumarin monomer and modified basalt fiber improves the impact resistance and impact strength, and the activation and modification of basalt also improves its dispersibility in epoxy resin and the effect of improving the impact resistance; at the same time, micro-arc oxidation of aluminum alloy and the addition of 3-aminopropyltriethoxysilane in the electrolyte effectively improve the bonding strength.

[0111] Test Example 2:

[0112] Salt spray resistance test: This paper conducts a neutral salt spray test on the prepared salt spray resistant high-strength aluminum alloy in accordance with GB / T 10125-2021. The four sides and back of the sample are sealed with red glue. The sample is placed in the salt spray chamber at 15-25° to the vertical direction. The test solution is 5wt% sodium chloride solution, and the salt spray settling speed is 80cm 2 The area was 2mL / h, the temperature in the salt spray chamber was 35±2℃, the pH value of the solution was between 6.5 and 7.2, and the total test time was 1800h. After the test, the surface corrosion conditions were rated in accordance with GB / T 6461-2002. Five specimens were tested in each group and the lowest grade was recorded.

[0113] The results are shown in Table 2.

[0114] Table 2

[0115] Salt spray corrosion grade Salt spray corrosion grade Example 1 8 Comparative Example 1 6 Example 2 9 Comparative Example 2 8 Example 3 8 Comparative Example 3 3 Comparative Example 4 6 Comparative Example 5 5 Comparative Example 6 7 Comparative Example 7 7

[0116] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 7 in Table 2, it can be found that the salt spray resistant high-strength aluminum alloy prepared in the present invention has good salt spray corrosion resistance.

[0117] By comparing the data in the table, it can be seen that the addition of epoxide imine monomer and modified basalt fiber effectively improves the ability to resist salt spray corrosion. At the same time, the activation and modification of basalt fiber effectively improve its salt spray resistance.

[0118] Test Example 3:

[0119] Water contact angle test: Use a contact angle tester to test the contact angle of pure water on the coating surface, and take the average value of five points each time.

[0120] The results are shown in Table 3.

[0121] Table 3

[0122] Water contact angle Water contact angle Example 1 134.24° Comparative Example 1 131.45° Example 2 135.67° Comparative Example 2 130.56° Example 3 133.59° Comparative Example 3 52.46° Comparative Example 4 122.38° Comparative Example 5 82.54° Comparative Example 6 131.26° Comparative Example 7 132.48°

[0123] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 7 in Table 3, it can be found that the salt spray resistant high-strength aluminum alloy prepared in the present invention has good surface hydrophobicity.

[0124] By comparing the data in the table, it can be seen that the addition of modified basalt fiber effectively improves the hydrophobic performance. The hydrophobic surface reduces the adhesion time of corrosive substances on the surface and has an effect on improving the corrosion resistance.

[0125] Test Example 4:

[0126] Self-healing performance test: Use a scalpel to cut scratches on the surface of the sample coating of the prepared salt spray resistant high-strength aluminum alloy and mark them. Use a microscope to observe and record the width of the scratches at the mark. Use two different wavelengths of ultraviolet light greater than 300nm and less than 300nm to alternately irradiate the scratches on the coating to repair them. Alternate every 30 seconds, and the total repair time is 12 hours. Measure and record the scratch width again, and record the remaining scratch width ratio. Then measure the scratch width every 1 hour of repair until it is zero, and record the complete repair time. Test 5 samples in each group and take the average value for recording.

[0127] The results are shown in Table 4.

[0128] Table 4

[0129] Remaining scratch width ratio Full repair time Example 1 4.67% 13h Example 2 1.24% 13h Example 3 2.56% 13h Comparative Example 1 37.48% 20h Comparative Example 2 48.67% 25h Comparative Example 3 3.44% 13h Comparative Example 4 2.87% 13h Comparative Example 5 5.42% 13h Comparative Example 6 3.89% 13h Comparative Example 7 2.67% 13h

[0130] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 7 in Table 4, it can be found that the salt spray resistant high-strength aluminum alloy prepared in the present invention has good self-repairing performance.

[0131] By comparing the data in the table, it can be seen that the addition of epoxide imine monomer and aminocoumarin monomer effectively improves the self-healing performance, and the repair conditions of both do not require heating and can be carried out at room temperature.

[0132] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A salt spray resistant high-strength aluminum alloy, characterized in that: The salt spray resistant high-strength aluminum alloy is made by spraying a modified epoxy resin spray liquid on the surface of a micro-arc oxidized aluminum alloy; The micro-arc oxidation aluminum alloy is prepared by pre-treating the aluminum alloy and then subjecting it to micro-arc oxidation process; The modified epoxy resin spraying liquid is prepared by mixing epoxide imine monomer, epoxy resin, modified basalt fiber, anhydrous ethanol, aminocoumarin monomer and polyetheramine; The epoxide imine monomer is prepared by reacting 5-hydroxymethylfurfural with decanediamine and then with epichlorohydrin; The modified basalt fiber is prepared by activating the basalt fiber after pretreatment and then modifying it with a coupling agent; The aminocoumarin monomer is prepared by reacting m-aminophenol with ethyl acetoacetate.

2. The salt spray resistant high-strength aluminum alloy according to claim 1, characterized in that: The aluminum alloy is a 7xxx series aluminum alloy.

3. The salt spray resistant high-strength aluminum alloy according to claim 1, characterized in that: The epoxy resin model is E-51, and the polyetheramine model is polyetheramine D-230.

4. A method for preparing a salt spray resistant high-strength aluminum alloy, characterized in that: The method comprises the following preparation steps: (1) The aluminum alloy is cut into the specified specifications of the product, and polished step by step under the conditions of 60#, 300#, 1000#, and 2000# sandpaper until the surface of the sample is free of scratches and smooth, and then ultrasonically cleaned and degreased with acetone solution, rinsed with ethanol and deionized water, and dried to obtain aluminum alloy samples; (2) Immerse the aluminum alloy sample in the electrolyte, connect the circuit, turn on the cooling water, set the parameters according to the micro-arc oxidation process requirements, start micro-arc oxidation, remove the cooling water after the reaction is completed, turn off the power and take it out, ultrasonically clean it in pure water for 3 to 4 times, each time for 8 to 10 minutes, and dry it in an oven at 100 to 120° C. for 8 to 10 hours to obtain a micro-arc oxidized aluminum alloy; (3) Melting 26 to 28 parts of 5-hydroxymethylfurfural at 50 to 60° C. by mass, adding 17 to 18 parts of decanediamine in 8 to 10 portions, reacting at 105 to 110° C. and 200 to 300 r / min for 1 to 1.5 hours after all the addition, cooling naturally to room temperature, washing with pure water and petroleum ether for 2 to 3 times respectively, and vacuum drying at 80 to 90° C. for 10 to 12 hours to obtain an imine monomer; (4) By weight, 45-46 parts of epichlorohydrin, 48-49 parts of imine monomer, and 0.8-0.9 parts of tetrabutylammonium bromide were mixed uniformly, reacted at 80-85° C. and 300-400 r / min for 2-3 hours, cooled naturally to room temperature, and 24-25 parts of 40wt% sodium hydroxide solution were added dropwise within 30 minutes, and 25-28 parts of butyl acetate were added at the same time. After the addition was completed, stirring was continued for 1-1.5 hours, filtered, and the filtrate was reprecipitated with petroleum ether and then filtered. All precipitates were washed once with ethanol, and then washed 3-4 times with pure water, and vacuum dried at 70-80° C. for 8-10 hours to obtain an epoxy imine monomer; (5) By weight, 10.9-11.7 parts of m-aminophenol are dissolved in 40-45 parts of dioxane, 5-6 parts of concentrated sulfuric acid are added dropwise at a rate of 1-2 drops per second, and 13-14 parts of ethyl acetoacetate are added dropwise at the same rate, and the mixture is reacted at 60-70° C. in a water bath at 300-400 r / min for 6-8 hours, cooled naturally to room temperature, and then precipitated in an ice water bath for 2-3 hours, filtered, and vacuum dried at 60-70° C. for 6-8 hours, recrystallized with ethyl acetate, and then vacuum dried once to obtain an aminocoumarin monomer; (6) By weight, 10 to 15 parts of the pretreated basalt fiber and 90 to 100 parts of the activation solution were mixed evenly, stirred at 80 to 90° C. and 300 to 400 r / min for 2 to 3 hours, filtered, ultrasonically cleaned with pure water for 3 to 4 times, each time for 4 to 5 minutes, and dried in an oven at 105 to 110° C. for 10 to 12 hours to obtain activated basalt fiber; (7) Add 10 to 15 parts of activated basalt fiber to 80 to 90 parts of coupling agent solution by weight, ultrasonically disperse for 20 to 30 minutes, stir at 70 to 75° C. and 200 to 300 r / min for 4 to 5 hours, filter, wash with pure water for 3 to 5 times, and vacuum dry at 80 to 90° C. for 8 to 10 hours to obtain modified basalt fiber; (8) By weight, 2 to 3 parts of epoxide imine monomer, 3 to 4 parts of epoxy resin, 1.5 to 2 parts of modified basalt fiber, and 70 to 80 parts of anhydrous ethanol are mixed uniformly, and ultrasonically dispersed at room temperature for 50 to 60 minutes, and 1 to 2 parts of aminocoumarin monomer and 2 to 3 parts of polyetheramine are added, and ultrasonically dispersed at room temperature for 30 to 40 minutes to prepare a modified epoxy resin spray liquid; (9) The modified epoxy resin spray liquid is sprayed on the surface of the micro-arc oxidized aluminum alloy with a spray gun, the spraying distance is controlled at 10 to 15 cm, the spraying pressure is 0.3 MPa, the coating thickness is controlled at 140 to 160 μm, and after spraying, it is cured at a constant temperature of 60° C. for 40 to 48 hours to obtain a salt spray resistant high-strength aluminum alloy.

5. The method for preparing a salt spray resistant high-strength aluminum alloy according to claim 4, characterized in that: The electrolyte in step (2) comprises the following components: 9-10 g / L sodium silicate, 3-4 g / L sodium hydroxide, 1-1.5 g / L sodium fluoride, 0.02 mol / L 3-aminopropyltriethoxysilane, and 2 g / L hydrogen peroxide.

6. The method for preparing a salt spray resistant high-strength aluminum alloy according to claim 4, characterized in that: The micro-arc oxidation process parameters in step (2) are mainly as follows: using a pulse power supply, a unidirectional pulse mode, and a current density of 8 to 10 A / dm 3 , time 30~40min, frequency 500Hz, duty cycle 10%.

7. The method for preparing a salt spray resistant high-strength aluminum alloy according to claim 4, characterized in that: The pretreatment process of the basalt fiber in step (6) is to crush the basalt fiber with a crusher and screen out the basalt fiber with a length of 100 to 200 μm with a screen.

8. The method for preparing a salt spray resistant high-strength aluminum alloy according to claim 4, characterized in that: The activation solution in step (6) is prepared by mixing 98 wt % concentrated sulfuric acid and 30 wt % hydrogen peroxide solution in a volume ratio of 7:

3.

9. The method for preparing a salt spray resistant high-strength aluminum alloy according to claim 4, characterized in that: The coupling agent solution in step (7) is prepared by uniformly mixing anhydrous ethanol, pure water, 3-aminopropyltriethoxysilane and dodecyltriethoxysilane in a mass ratio of 90:10:1:1 and then ultrasonically dispersing for 3 to 5 minutes.

10. The method for preparing a salt spray resistant high-strength aluminum alloy according to claim 4, characterized in that: The modified epoxy resin spraying liquid in step (8) can also be prepared into corresponding coatings according to the process requirements of scraping, dripping and brushing, and applied by scraping, dripping and brushing.